EVALUASI KINERJA STRUKTUR PADA GEDUNG BERTINGKAT DENGAN ANALISIS DINAMIK RESPON SPEKTRUM MENGGUNAKAN SOFTWARE ETABS ( STUDI KASUS : HOTEL DI WILAYAH KARANGANYAR ) - Muhammad Luthfi Rifai; Agus Setiya Budi; Wibowo Wibowo (Program Studi Teknik Sipil FT UNS, 2014)
Indonesia is located at the junction of the earth's tectonic plates, namely the Eurasian tectonic plates, the Pacific, the Philippines, andIndo - Australian. Besides, Indonesia also has many volcanoes which are still active, so that Indonesia is a country that is prone toearthquakes. The earthquake effects on damage to the building structure. Even it effects in fatalities because of the falling debris.When an earthquake occurs, it is expected that the building can withstand earthquake forces at a certain level without damage to thebuilding so it avoids earthquake victims. There are two analytical approaches that can be used to calculate the lateral loads on theearthquake. Those analysis are a static analysis and dynamic analysis. Dynamic analysis is used for the high buildings which has alot of levels. This analysis consists of dynamic response spectrum analysis and time history dynamic analysis. This study aims to investigatethe building structure performance based on displacement and drift. The method that is used in this study is the dynamic responsespectrum analysis by using ETABS. The maximum displacement of the building in the X direction is 0.0465 m and in theY direction is 0.0634 m, so that if it is viewed from the limit performance and the limit ultimate performance, it is categorized as aeligible building (safely) in accordance with SNI 3-1726-2002. The maximum total drift in the X direction is 0.00090 and the Ydirection is 0.00123. The maximum total inelastic drift in the X direction is 0.00077 and the Y direction is 0.00103, so thatwhen it is viewed according to ATC - 40, it is included in the level immediate occupancy category.